Carcass physical composition and physic-chemical characteristics of meat from Nellore cattle - Aline Kellermann de Freitas (Semina: Ciências Agrárias, 2016)
Assessment of carcass physical composition and physicochemical characteristics of meat from Nellore males distributed randomly into three treatments: males castrated at 13 months of age at puberty (n=26); castrated at 18 months of age, 15 days before confinement (n=26); and young bulls (n=25). For the evaluation of meat chemical characteristics, we used samples of 12 animals taken at random from each treatment. The experimental design was completely randomized. Animals were slaughtered at 22 months of age after 100 days of confinement. The carcasses of young bulls showed higher contents of muscle (66.46 %) and bone (16.03 %), and lower fat content (17.66 %), in relation to that of steers castrated at 13 (62.83,15.28, and 22.11 %, respectively) or 18 months (63.99, 15.29, and 21.53%, respectively), which did not differ amongst themselves. The meat of young bulls was darker (3.07 points) than the meat from those castrated at 13 months of age (3.43 points), while the meat from those castrated at 18 months displayed an intermediate color (3.29 points), not differing from the others. Young bulls yielded meat with lower content of intramuscular fat (3.18 points) and lipids (3.81%) in relation to those castrated at 13 (4.58 points and 6.77%, respectively) or 18 months (4.52 points and 5.66%, respectively). Protein content was higher (P<.05) in meat from steers castrated at 13 months in relation to young bulls. The shear strength of the muscle fibers was not altered (P> 0.05) by the age of castration, with young bulls having lower values in relation to the castrated males. Castration of Nellore young bulls in early puberty increases the edible portion of the carcass due to the higher body fat deposit.